Actin filaments regulate microtubule growth at the centrosome. (22nd March 2019) - Inoue, Daisuke; Obino, Dorian; Pineau, Judith; Farina, Francesca; Gaillard, Jérémie; Guerin, Christophe; Blanchoin, Laurent; Lennon‐Duménil, Ana‐Maria; Théry, Manuel
Abstract: The centrosome is the main microtubule‐organizing centre. It also organizes a local network of actin filaments. However, the precise function of the actin network at the centrosome is not well understood. Here, we show that increasing densities of actin filaments at the centrosome of lymphocytes are correlated with reduced amounts of microtubules. Furthermore, lymphocyte activation resulted in disassembly of centrosomal actin and an increase in microtubule number. To further investigate the direct crosstalk between actin and microtubules at the centrosome, we performed in vitro reconstitution assays based on (i) purified centrosomes and (ii) on the co‐micropatterning of microtubule seeds and actin filaments. These two assays demonstrated that actin filaments constitute a physical barrier blocking elongation of nascent microtubules. Finally, we showed that cell adhesion and cell spreading lead to lower densities of centrosomal actin, thus resulting in higher microtubule growth. We therefore propose a novel mechanism, by which the number of centrosomal microtubules is regulated by cell adhesion and actin‐network architecture. Synopsis: Centrosomes, the main interphase microtubule‐organizing centers of the cell, also nucleate local actin filament networks, which are now found to form a physical barrier blocking microtubule elongation. Activation of B lymphocytes is associated with reduction of centrosomal actin and increase in the number of microtubules. The amount of centrosomal actin is negatively correlated to the amount of microtubules. In vitro reconstitutions show negative correlation between the amount of centrosomal actin and the number of microtubules. Cell spreading proportionally affects the amount of centrosomal actin and the number of centrosomal microtubules. Abstract : Increasing density of F‐actin nucleating from the main interphase microtubule‐organizing center creates a physical barrier for nascent microtubules in lymphocytes and in vitro .